DOUBLE TRACK SANCTION SYSTEM FOR MISUSE OF CLASS I NON-PLANTS NARCOTICS - Geovanni Villarba Gamas (Journal of International Islamic Law, Human Right and Public Policy, 2024)
This article is entitled "Double Track Sanction System Against Narcotics Abuse Class I Not Plants". The thesis with this title aims to know and examine the double track sanction system against narcotics abuse class I not plants and the legal politics of the double track sanction system against narcotics abuse class I not plants. This research is a normative research with a legal political approach. The data source is secondary data consisting of primary legal materials and secondary legal materials. The data collection method uses a literature study. Primary legal materials and secondary legal materials are analyzed using legal analysis methods. The thinking process used to draw conclusions, namely the deductive thinking process. The role of the double track sanction system for the abuse of narcotics class I is not a plant, especially we find in Law Number 35 of 2009 concerning Narcotics and Law Number 1 of 2023 concerning the Criminal Code. There are differences in the regulation of the double track system because there are differences in the concept of the system in the Law governing this matter. The double track system in Indonesia should be developed to provide alternative punishment for drug abusers. The renewal of the Double Track System arrangement can be done by considering the legal system and legal principles applicable in Indonesia. This will enable the creation of legal certainty and provide justice for victims of drug abusers.